Reproductive performance and survival of young one-humped camels on Kenya commercial ranches - Wilson, R.T. (Cambridge University Press, 1986)
Examines the reproductive performance and survival of young one-humped camels (Camelus dromedarius) on Kenya commercial ranches. Includes data on seasonality of breeding, age at first parturition, parturition interval, sex ration, gestation period, and early survival.